Impact of Implementing the Quality of Electronic Services on the Satisfaction of Princess Noura University from the Students’ Point of View - Almohareb, Noha; AlAdaileh, Ali (Jordan Journal of Business Administration, 2017)
This study aimed to identify the impact of implementing the quality of electronic services on the satisfaction of Princess Noura University students provided to them by the University site on the World Wide Web (Internet). To achieve the objective of the study, a questionnaire has been used as a tool for information gathering. 500 questionnaire forms have been distributed to the University’s students in various disciplines and academic levels in a random manner. 306 of them have been restored and were valid for statistical analysis at a rate of 61.2%. In addition, primary sources, such as books and scientific articles, were utilized. After the process of collecting information, the questionnaires, were coded, entered into a computer and processed statistically using the Statistical Package for Social Sciences (SPSS). Frequencies, means, standard deviations, variance analysis and multiple regression were used. The study concluded that there is a little quality of electronic services provided by the University of Princess Nora from the students’ point of view. Also, there is a weak level of satisfaction by the students toward those electronic services provided by the University of Princess Noura. The study indicated the presence of a statistically significant impact on the application of the quality of electronic services provided by the University of Princess Noura standards on the level of satisfaction of the students with these services. The study recommended to continue to conduct further studies, in an attempt to measure more accurately the quality of electronic services, along with the reconsideration of the efficiency of the University of Princess Noura site in terms of providing information in a way that helps the students to get the desired information with minimal effort. It also recommended the development of the University’s website to make it easy for the students to perform the academic movements through the site without having to personally attend the University.